Ügijn san sudlal - Nansalmaa, Njamžavyn (Udam Soël HHK, 2015)
Research on Mongolian lexicology
Keywords: Mongolian language / Lexicography; Mongolian language / Semantics; Mongol (Langue) / Lexicographie; Mongol (Langue) / Sémantique; Mongolisch; Sprache; Semantik; Lexikografie